Microsatellite primers in Parietaria judaica (Urticaceae) to assess genetic diversity and structure in urban landscapes1. (9th September 2014) - Bossu, Angèle; Bertaudière‐Montès, Valérie; Dubut, Vincent; Manel, Stéphanie
Abstract : Premise of the study: Urbanization is one of the main factors contributing to loss of genetic diversity, as the resulting landscape fragmentation and habitat loss induce species isolation. However, studies of genetic structure and diversity in urbanized landscapes are still rare. We characterized microsatellite primers for Parietaria judaica to study this environment. Methods and Results: Eleven microsatellite loci from P. judaica, an urban plant, were isolated using shotgun pyrosequencing, and the simple sequence repeat (SSR) markers were screened in 20 individuals of P. judaica . The loci were tested on 166 individuals from three populations in different cities. The number of alleles ranged from two to 19, and expected and observed heterozygosity values ranged from 0.019 to 0.912 and 0.019 to 0.448, respectively. Conclusions: The markers amplified well in the species and will be useful for examining genetic diversity and population genetic structure in this urban plant.